Perancangan Aplikasi E-Commerce Toko CibitungSecond Berbasis Website - Pratama, Satrio Aji; Sari, Rafika (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
Competition in the clothing sales business in the city of Bekasi is getting tougher. CibitungSecond is a clothing store located in the city of Bekasi. The sales system mechanism at this store still uses a conventional system, where customers must come directly to the store. With the E-Commerce website at the CibitungSecond store, it is hoped that it will make it easier for customers to purchase products without having to come to the place, as well as expand marketing and develop customer loyalty. This shop was developed with software used to design and design E- Commerce websites, namely the PHP programming language, text editor, MySQL database. This website can also generate information on products that are sold, as well as provide reports aimed at store admins such as product reports, customer reports, order reports, and sales reports.